2018
DOI: 10.1371/journal.pone.0199944
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of library and information services in Japan: The detailed use and value of information in clinical settings

Abstract: ObjectivesConsidering that there is a lack of evidence regarding the contribution of library and information services to evidence-based medicine in actual clinical practice in Japan, the purpose of the study is to explore the current status of use and value of library and information services in clinical settings to examine the usefulness of information in implementing evidence-based medicine (EBM) into practice.MethodsA Web-based survey was conducted at seven sites (hospitals with 300–1,200 beds) and intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Indeed, there is research that investigates the information seeking behaviours of HPs that shows that they assign different value to different information resources depending on it being physical textbooks or electronically available research articles [ 44 ]. Interestingly enough this Japanese study identified a difference between nurses more often choosing printed resources and doctors preferring electronic ones.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is research that investigates the information seeking behaviours of HPs that shows that they assign different value to different information resources depending on it being physical textbooks or electronically available research articles [ 44 ]. Interestingly enough this Japanese study identified a difference between nurses more often choosing printed resources and doctors preferring electronic ones.…”
Section: Discussionmentioning
confidence: 99%
“…We explored the experience of Italians who lived the quarantine, adopting the Critical Incident Technique (CIT) [ 18 , 19 ]. It is a well-established qualitative research tool used in many studies in services evaluation [ 20 23 ], patient perspective in the healthcare context [ 24 , 25 ] or meaningful life experiences [ 26 , 27 ] but, to our knowledge, has still not applied to the context of the lockdown. In this study, we adapted this technique to focus on relevant positive and negative episodes representing individuals’ experience during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In another study on the clinical utility of library and information services in Japan which was carried out with the help of 598 physicians, residents and nurses, using CIT, a web-based questionnaire and interviews, the participants claimed that using information in most cases prevented additional procedures and testing (37.2%), adverse drug reaction or interaction (33.8%), patient misinterpretation of disease (25.9%), misdiagnosis (7.9%), hospital admission (6.9%), patient mortality (5.4%), surgery (5.7%), nosocomial infection (4.4%) and medical errors (2.8%) (Sakai et al, 2018).…”
Section: Objectives Question and Answer Strategy Studiesmentioning
confidence: 99%
“…They responded to the questions based on the recall technique. For example, to examine the clinical usefulness of the library and information services, Sakai et al (2018) used CIT to observe the behaviour of physicians, residents and nurses about specific clinical care for a period of 6 months. In this study, the participants were asked about the type of information they used, information resources, search locations and access points, as well as the value of information.…”
Section: Investigating the Clinical Staff's Information-seeking Behav...mentioning
confidence: 99%